الإضرار بالزوجة في ولاية سلانجور : دراسة في ضوء الفقه الإسلامي - ساما، حفصه حاج
This research was conducted using the descriptive, analytical, and statistical methods on the phenomenon of harming wife in the state of Selangor in Malaysia as a case study. The study exhaustively defined the concept of harming, its sources, causes, and negative effects on the wife. The finding reveals the ignorance of some spouses about the explanation of the Quranic verses relating to guardianship and beaten wife. It also shows substantial number of cases involving harming wife in Selangor. There are many causes of harming wife, and some of the main causes were lack of awareness and financial problems. The study also shows that in Malaysia there were two types of jurisdictions (courts); one is legitimate for Muslims and the other for the general population. The affected wives were at liberty to seek redress of their cases at either in courts or in specific situations. Comparing the punishment of the two courts (Shari'ah and civil courts), it is eminent that the civil courts render more effective decision than the Shari'ah courts. Generally, in executing their activities, all religious institutions should give greater consideration in protecting the interest of women based on the Shari'ah maxim, “Hardship must be prevented”. The interviews and the field work show that the issue of extreme harming wife is quite minimal, as most wives did not report to the authorities due to the restraint placed upon them by customs and families. The researcher recommends the need for awareness among women to keep them informed about their rights, especially, if they are deprived of these rights. She also recommends that the Shari'ah courts should consider revising the punishments in order to protect the rights of women and to deter irresponsible men, and the ignorant ones from perpetrating these offences.